Peredaran Pakaian Bekas Ditinjau Dari UU Perlindungan Konsumen - Abdullah, Mayanti H.; Dungga, Weny Almoravid; Kamba, Sri Nanang Meiske (CV. ITTC INDONESIA, 2023)
The use of used goods has had a significant impact on the local economy, driving market growth and increasing the accessibility of fashion products for consumers with limited budgets. The purpose of this research is to find out how legal protection is for consumers who use used goods or used clothes. This research uses a type of literature study research. Literature study is a type of research conducted by collecting and analyzing information from existing literature sources. The use of used goods or used clothing requires better legal protection for consumers. Clear regulations, strict supervision, consumer education, and improving the quality of sellers are steps that can be taken to increase legal protection for consumers who use thrift fashion goods in this market.